Competition and Cooperation: A Scope Study on the Development Path and Competition Strategy of Film Industry in China / Liu Ting Lei, Mohd Feroz Shah De Costa Mohd Faris De Costa and Megat Al Imran Yasin - Liu, Ting Lei; Mohd Faris De Costa, Mohd Feroz Shah De Costa; Yasin, Megat Al Imran (Universiti Teknologi MARA, Cawangan Melaka, 2013)
The Chinese film industry is currently undergoing a rapid developmental phase. During this period, it is influenced not only by Hollywood but also by other global film markets. Moreover, domestic cross-border investments are showing a trend of diversification, and the competition within the film industry is particularly fierce. For the Chinese film sector to prosper in this environment, it is crucial to enhance its core competitiveness. This can be achieved through rigorous competitive strategies. This article provides a brief overview of the industry's development from a competitive strategy perspective, aiming to promote the sustainable growth of the Chinese film landscape. Special emphasis is placed on how to learn from international experiences, compete with them, and draw from these encounters. Additionally, the article delves into managing competitive relations within the industry to ensure the long-term healthy development of the film sector.